Peningkatan Kemampuan Hasil Belajar Peserta Didik Materi Aku Pribadi yang Unik dengan Menerapkan Model Pembelajaran Problem Based Learning di Kelas X SMK Negeri 2 Singkawang Tahun Pelajaran 2024 - Sutriani Sutriani (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Classroom Action Research (PTK) was carried out to improve student learning outcomes in Catholic Religious Education and Character Education subjects using the Problem Based Learning learning model. The purpose of writing this research is to find out: 1 obstacles faced in implementing the Problem Based Learning learning model. 2) implementation of the Problem Based Learning learning model, and 3) changes in student learning outcomes after implementing the Problem Based Learning learning model.The application of the Problem Based Learning learning model is carried out as follows: 1) orienting students to problems, 2) organizing student learning, 3) guiding individual and group investigations, 4) developing and presenting work results, and 5) analyzing and evaluating the problem solving process. The results of the research are that student learning outcomes increased by 83.57. The learning outcomes achieved showed a significant increase in the average learning outcomes, namely an increase of 9.64. The learning process using the Problem Based Learning learning model provides better results and can be used in an effort to improve learning outcomes in learning at SMK Negeri 2 Singkawang.